Political media framing strategies of 'Keling' - Abdul Rahim Seth, Nurul Sofia Seth; Sahar, Rafidah (Kulliyyah of Languages & Management (KLM) International Islamic University Malaysia, 2021)
In political communication field, framing is a concept referring to journalistic point of view that emphasises one aspect of political issue over another. Framing has powerful shaping influences on the audience’s interpretation of issues, events and individuals. In politics, framing can serve as a strategic move for candidates or parties, which in turn can affect their performance in opinion polls. Against this background, this paper presents research findings of a qualitative-based study on the news and social media’s framing of ‘Keling’ in Malaysian politics. The usage of ‘keling’ is considered as an ethnic slur in Malaysian society. When Tun Dr Mahathir Mohammad, the then former Malaysian Prime Minister, mentioned the word ‘keling’ in his speech, it has caused a ruckus in the news and social media. Based on the News Framing theory, a thematic analysis was conducted on news and social media in the period surrounding the event to determine the usage of news frames of ‘Keling’. This paper concludes that research findings of the study might contribute significantly to the knowledge of framing studies in political communication.